Cultural safety in radiation therapy education: Identifying knowledge deficits to improve Indigenous health practice - Thashmira Naidoo; Crispen Chamunyonga; Julie Burbery; Peta Rutledge (Journal of Medical Radiation Sciences)
Abstract Reducing health disparities for Aboriginal and Torres Strait Islander peoples requires the integration of cultural safety into healthcare education. This commentary paper addresses cultural safety in the context of the radiation therapy profession and emphasises the importance of making practitioners aware of the knowledge gaps in healthcare practice. The educational strategies to improve cultural awareness amongst undergraduate students and qualified radiation therapists (RTs) are explored. The authors propose a range of recommendations to enhance cultural awareness amongst RTs in the context of Indigenous Australian care, aimed at promoting improved experiences for Aboriginal and Torres Strait Islander peoples receiving cancer care. Curriculum integration and development of initiatives such as workshops and interactive yarning groups are highlighted as pivotal platforms that foster continuous learning in radiation therapy.